Awareness and knowledge of HIV/AIDS in school going children of Surat, Gujarat - Kariya, Prashant; Shringarpure, Kalpita S.; Patel, Apurva G. (International Journal Of Community Medicine And Public Health, 2023)
Background: Adolescents are susceptible to unhealthy practices due to a lack of knowledge and curiosity to try new things. Adolescent age also forms the base for behaviors throughout their lives. This study therefore aimed to understand adolescents’ present knowledge and attitude towards HIV/AIDS. Methods: A questionnaire was created with knowledge and attitude-based questions regarding HIV/AIDS. The questionnaire was embedded in google Forms and was sent via WhatsApp, to collect responses from school going children of age 14 to 18. Ethical permissions and consents were taken and the data collection went on for a week. Results: 2000 children took part in the study, out of that 732 were males and 1268 were females. The mean score of all the participants was calculated to be 68.52% with a standard deviation of 17.18. There was no statistical significance of gender and the mean score of the participants, whereas statistical significance was found for age-wise distribution of mean score. Participants scored well on basic knowledge-based questions like “causative organism’’ but failed to do good on little complicated questions like ‘’Route of transmission’’ Conclusions : The results from this study can be applied to similar regions of Gujarat and other states as well. This would help in making changes in the education of this age group of children. Such studies also form the base of future studies to evaluate the difference in knowledge of the school going children over a period of time by comparing this data.